Determinants of community-based participatory small ruminant breeding program: evidence from smallholder goat producers in pastoral areas of Southern Ethiopia - Kutoya Gemede Kusse; Mesele Jobir Dagne (Cogent Food & Agriculture)
Community-based smallholder goat producers’ participation in breeding programs is a means of improving the production and productivity of their goats, but nowadays it does not yield significant results in pastoral and agro-pastoral areas. This is due to many determining factors, that smallholder goat producers do not participate in community-based breeding programs (CBBPs). In Ethiopia, studies tried to identify the determining factors that influence smallholder goat producers’ participation in CBBP but did not address the problem in the study area. As a result, this research aimed to identify the determinants of community-based goat breeding programs in the study area. A semi-structured interview schedule, focus group discussions and key informant interviews were used to gather primary data. Primary data about the study was collected from 138 sample households. The study was conducted in the Bena-tsemay district of southern Ethiopia. A probit regression model was used to analyze determinants of smallholder goat producers’ participation in CBBP. In the probit regression among 13 identified independent variables, age, goat farming experience, access to credit and distance to training center influence CBBP participation at (p < .01). Education status and veterinary service problems influence CBBP participation at (p < .05) significance level. To strengthen CBBP, government lead investment in goat breeding is important.